COMPETITIVE ADVANTAGE STRATEGIES AND CULINARY BUSINESS SUCCESS - Herminda, Herminda; Muksin, Abdullah (Dinasti International Journal of Digital Business Management, 2021)
This study examines the problems of the success of culinary businesses that have not been done much, especially during this covid 19 pandemic. The purpose of this study is to determine and analyze the effect of business competence, financial governance and competitive advantage on the success of culinary businesses in Jakarta. To achieve the success of the culinary business, a competitive advantage strategy is needed by increasing the competence of business actors and financial governance. The object of this research is culinary business in 10 culinary center locations in DKI Jakarta with a selected population of 1,216 culinary entrepreneurs and a total sample of 257 respondents. The data analysis tool used is Structural Equation Modeling (SEM) with the Lisrel 8.80 . program. The results of this study prove firstly that the magnitude of the contribution of the influence of business competence and financial governance together on the competitive advantage of culinary businesses is 82%, while the remaining 18% is the influence of other variables. While the second is that the magnitude of the contribution of the influence of business competence, financial governance and competitive advantage together on business success is 86%, while the remaining 14% is the magnitude of the influence of other variables. The most dominant variable influencing business success is the competitive advantage variable variabel.